2010
DOI: 10.3109/15376516.2010.497975
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the ability of newly-developed bispyridinium oxime K203 and currently available oximes (trimedoxime, obidoxime, HI-6) to counteract the acute neurotoxicity of soman in rats

Abstract: The neuroprotective effects of newly-developed oxime K203 and currently available oximes (trimedoxime, obidoxime, HI-6) in combination with atropine in rats poisoned with soman were studied. The soman-induced neurotoxicity was monitored using a functional observational battery at 24 h following soman challenge. The results indicate that the potency of a newly-developed oxime K203 to counteract soman-induced neurotoxicity is very low and roughly corresponds to the neuroprotective efficacy of currently available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The acquired filtrate was subsequently analyzed according to previously published methods [31,32]. AUC from the control sample was considered as a reference value of 100%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The acquired filtrate was subsequently analyzed according to previously published methods [31,32]. AUC from the control sample was considered as a reference value of 100%.…”
Section: Resultsmentioning
confidence: 99%
“…However, C max is reached only after a relatively long time, which could be a disadvantage when rapid reactivation is needed especially against quickly aging AChE inhibitors (e.g., soman). Nevertheless, HI-6 is the only available oxime so far to show some efficacy against soman intoxication [32]. The C max time delay seems to be of importance, since obidoxime reaches C max swiftly when compared to the other compounds and has relatively rapid elimination from the plasma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attachment of substituents to the pyridinium ring [e.g. malonyl, not shown here (Hassan et al, 2009)] induced changes in charge distribution [fluoride, not shown here (Okamura et al, 2005;Jeong et al, 2009;Kassa et al, 2010a)] or the introduction of alkyl and halogen substituents could also increase the lipophilicity, resulting in improved blood-brain distribution.…”
Section: Facilitation Of Bbb Penetrationmentioning
confidence: 99%
“…The reactivating potency of the newly synthesized pyridinium mono‐aldoximes (K156 and K203) were compared with that of the classic mono‐ and bis‐aldoximes (Kassa et al ., ). Based on in vivo experiments in rats, it appears that there are two PyAls with superior antidotal effects, namely K027, which shows convincing efficacy in increasing the survival rate after exposure to organophosphate pesticides (Petroianu & Kalász, ), and K203, with good AChE regenerating properties on acetyl cholinesterase inhibition by cyprofos and tabun (Musilek et al ., , , ; Kassa et al ., , ).…”
Section: Introductionmentioning
confidence: 99%